Method and apparatus for manufacturing membrane catalyst layer assembly
By applying a catalyst ink to an electrolyte membrane, drying it, and using a pressing member with low adhesive force and a mold-release member during the heating and pressing treatment, the method effectively reduces catalyst layer transfer and membrane adhesion, ensuring efficient catalyst deposition and membrane conveyance.
Patent Information
- Application Number
- JP2023150278
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
During the heating and pressing treatment of membrane catalyst layer assembly, the catalyst layer can be transferred to the heat roller, and the electrolyte membrane can adhere to it, leading to contamination and insufficient catalyst deposition on the membrane.
The method involves applying a catalyst ink to an electrolyte membrane, drying it to form a catalyst layer, and then pressing and heating the assembly using a pressing member with an adhesive force of 0.5 N/cm or less to the catalyst layer and electrolyte membrane, and using a mold-release member to prevent adhesion.
This approach reduces the transfer of the catalyst layer to the pressing member and the adhesion of the electrolyte membrane to the pressing member, ensuring a sufficient catalyst layer on the membrane and facilitating the conveyance of the electrolyte membrane.
Smart Images

Figure 2025043012000001_ABST
Abstract
Description
[Technical field]
[0001] The subject matter disclosed herein relates to a method and apparatus for producing a membrane / catalyst layer assembly. [Background technology]
[0002] Catalyst-Coated Membrane (CCM) is used in energy conversion technologies such as fuel cell technology and electrolytic hydrogen production technology. CCM has high catalytic activity, which promotes reactions in fuel cells and electrolytic hydrogen production cells, achieving high electricity generation efficiency. This improves the efficiency of the energy conversion process and reduces power loss. In addition, energy conversion technologies such as fuel cells do not generate CO2, so they have a lower environmental impact than combustion-based energy conversion. Therefore, the use of CCM can reduce the burden on the environment.
[0003] In the manufacturing process of such a CCM, a catalyst ink containing water and alcohol as a solvent is applied to an electrolyte membrane, and then the applied catalyst ink is dried. Then, the catalyst layer, which is the layer of the dried catalyst ink, may be subjected to a heat and pressure treatment with a hot roller to modify the catalyst layer, for example by improving its adhesion to the electrolyte membrane (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-153653 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the heat pressing process, the catalyst layer is heated to a temperature exceeding the glass transition point (approximately 100 to 120°C) of the ionomer contained in the catalyst ink, thereby maximizing the effect of improving the adhesion of the catalyst layer to the electrolyte membrane. However, there are problems with heating, such as the catalyst layer being transferred to the heat roller or the electrolyte membrane being stuck to the heat roller. If the catalyst ink is transferred to the heat roller, the heat roller may be contaminated, and the amount of catalyst on the electrolyte membrane may be insufficient. Furthermore, if the electrolyte membrane is stuck to the heat roller, there is a risk that it may become difficult to transport the electrolyte membrane.
[0006] An object of the present invention is to provide a technique that can reduce the transfer of a catalyst layer to a pressing member and the sticking of an electrolyte membrane to the pressing member during a heat and pressure treatment. [Means for solving the problem]
[0007] In order to solve the above problem, a first aspect includes a coating process of coating a catalyst ink onto an electrolyte membrane, a drying process of drying the catalyst ink coated onto the electrolyte membrane by the coating process to form a catalyst layer, and a pressing and heating process of pressing and heating the electrolyte membrane with the catalyst layer formed thereon after the drying process with a pressing member, wherein the adhesive force of the pressing member to the electrolyte membrane and the catalyst layer is 0.5 N / cm or less.
[0008] A second aspect is a method for manufacturing a membrane catalyst layer assembly of the first or second aspect, wherein the pressing member has a pressing main body and a releasable member having an adhesive force with respect to the electrolyte membrane and the catalyst layer that is smaller than that of the pressing main body, and the pressing member presses the electrolyte membrane via the releasable member with the pressing main body in a state where the releasable member is in contact with the electrolyte membrane.
[0009] A third aspect is the method for producing a membrane / catalyst layer assembly according to the second aspect, wherein the releasable member is fixed to a surface of the pressing body.
[0010] A fourth aspect is a method for producing a membrane / catalyst layer assembly of the second or third aspect, wherein the releasable member is a sheet-shaped release sheet, and the press heating step includes a step of supplying the release sheet between the catalyst layer and the electrolyte membrane, and the press main body portion.
[0011] A fifth aspect is the method for producing a membrane / catalyst layer assembly according to the third or fourth aspect, in which the material of the releasable member contains a heat-resistant polymer.
[0012] A sixth aspect is a method for producing a membrane catalyst layer assembly of the third or fourth aspect, wherein the pressing body includes a pair of heated rollers whose surfaces are heated, and the pressing and heating step includes a step of sandwiching the catalyst layer and the electrolyte membrane between the pair of heated rollers.
[0013] A seventh aspect is an apparatus for manufacturing a membrane catalyst layer assembly, comprising: a transport mechanism for transporting an electrolyte membrane; a coating unit for applying a catalyst ink to the electrolyte membrane being transported by the transport mechanism; a drying unit for drying the catalyst ink applied by the coating unit to form a catalyst layer; and a pressing and heating unit for pressing and heating the catalyst layer and the electrolyte membrane with a pressing member, wherein the adhesive force of the pressing member to the catalyst layer and the electrolyte membrane is 0.5 N / cm or less. Effect of the Invention
[0014] According to the manufacturing methods of the membrane catalyst-layer assembly of the first to sixth aspects and the manufacturing apparatus of the membrane catalyst-layer assembly of the seventh aspect, the adhesive strength of the pressing member to the catalyst layer and the electrolyte membrane is 0.5 N / cm or less, so that the transfer of the catalyst layer to the pressing member and the sticking of the electrolyte membrane to the pressing member can be reduced.
[0015] According to the second aspect of the method for producing a catalyst-coated membrane assembly, pressing with the pressing body through a releasable member can reduce transfer of the catalyst layer to the pressing member and sticking of the electrolyte membrane to the pressing member.
[0016] According to the third embodiment of the method for producing a catalyst layer membrane assembly, even if the pressing member of the releasable member is brought into direct contact with the catalyst layer and the electrolyte membrane to press them, transfer of the catalyst layer and sticking of the electrolyte membrane can be reduced.
[0017] According to the fourth aspect of the method for producing a catalyst layer membrane assembly, the catalyst layer and the electrolyte membrane are pressed via a release sheet, which reduces the transfer of the catalyst layer to the pressing member and the sticking of the electrolyte membrane to the pressing member.
[0018] According to the fifth aspect of the method for producing a catalyst-coated membrane assembly, since the heat-resistant polymer is contained, the releasable member can have heat resistance, which can reduce deformation of the releasable member due to pressure.
[0019] According to the sixth aspect of the method for producing a catalyst-coated membrane assembly, the electrolyte membrane is sandwiched between a pair of heated rollers, whereby the catalyst layer and the electrolyte membrane can be pressed while being heated. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram showing a CCM manufacturing apparatus according to a first embodiment. [Diagram 2] FIG. 13 is a diagram showing a CCM manufacturing apparatus according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. Note that the components described in the embodiment are merely examples, and are not intended to limit the scope of the present invention. In the drawings, the dimensions and numbers of each part may be exaggerated or simplified as necessary for ease of understanding.
[0022] <1. First embodiment> 1 is a diagram showing a CCM manufacturing apparatus 1 according to the first embodiment. The CCM manufacturing apparatus 1 is an apparatus for manufacturing a catalyst layered membrane (CCM) by forming a catalyst layer of a catalyst ink on the surface of an electrolyte membrane 91 included in a strip-shaped laminated substrate 9 while continuously transporting the laminated substrate 9. The CCM manufacturing apparatus 1 includes a transport mechanism 10, an application section 20, a drying section 30, and a pressure heating section 40.
[0023] The transport mechanism 10 is a mechanism for continuously transporting the band-shaped laminated base material 9 in a transport direction along the longitudinal direction of the band-shaped laminated base material 9. The transport mechanism 10 includes an unwinding roller 11, a plurality of transport rollers 12, a winding roller 13, and a support roller 14.
[0024] The laminated base material 9 is wound in a roll shape around the unwinding roller 11. The laminated base material 9 is unwound from the unwinding roller 11 and transported along a transport path defined by a plurality of transport rollers 12. Each transport roller 12 rotates about a horizontal axis to guide the laminated base material 9 downstream of the transport path. The positions and number of the transport rollers 12 can be set as desired. After transport, the laminated base material 9 is collected by the take-up roller 13.
[0025] Here, the configuration of the laminated substrate 9 will be described. The laminated substrate 9 is formed by bonding an electrolyte membrane 91 and a back sheet 92 together. The electrolyte membrane 91 of the laminated substrate 9 is a thin film (ion exchange membrane) having ion conductivity. A fluorine-based or hydrocarbon-based polymer electrolyte membrane can be used for the electrolyte membrane 91, and specifically, a polymer electrolyte membrane containing perfluorocarbon sulfonic acid can be used. When the electrolyte membrane 91 is for a solid polymer electrolyte fuel cell, the thickness of the electrolyte membrane 91 is, for example, about 5 μm to 30 μm. When the electrolyte membrane 91 is for a solid polymer electrolyte water electrolysis, the thickness of the electrolyte membrane 91 is, for example, 50 μm or more, and preferably 150 μm to 300 μm.
[0026] The electrolyte membrane 91 has a first surface 911 and a second surface 912. The first surface 911 is a surface on which a catalyst ink is applied to form a catalyst layer 93 of the catalyst ink. The second surface 912 is a surface in contact with the back sheet 92 via an adhesive.
[0027] The back sheet 92 in the laminated base material 9 is a film for suppressing deformation of the electrolyte membrane 91. The electrolyte membrane 91 and the back sheet 92 are attached to each other via an adhesive. In this way, the electrolyte membrane 91 is supported by the back sheet 92. By handling the electrolyte membrane 91 while it is supported by the back sheet 92, rather than by itself, deformation of the electrolyte membrane 91 can be suppressed. Furthermore, by using the back sheet 92, the electrolyte membrane 91, which has low mechanical strength, can be transported without being damaged.
[0028] The back sheet 92 is a resin film having higher mechanical strength and excellent shape retention than the electrolyte membrane 91. PET (polyethylene terephthalate) can be used as the material of the back sheet 92. Also, instead of PET, PEN (polyethylene naphthalate), oriented nylon, oriented rigid polyvinyl chloride, OPP (oriented polypropylene), or the like can be used as the material of the back sheet 92.
[0029] The support roller 14 of the transport mechanism 10 supports the laminated substrate 9 in the coating section 20. The support roller 14 is a roller having a cylindrical or cylindrical substrate. The support roller 14 is located downstream of the unwinding roller 11 on the transport path and upstream of the drying section 30 on the transport path. The support roller 14 rotates about a horizontal axis while contacting the back sheet 92 of the laminated substrate 9.
[0030] The coating unit 20 has a coating nozzle 21, a liquid supply pipe 22, a catalyst ink supply source 23, and an on-off valve 24. The coating nozzle 21 faces a first surface 911 of an electrolyte membrane 91 in a laminated substrate 9 supported by a support roller 14. The laminated substrate 9 moves relative to the coating nozzle 21 due to the rotation of the support roller 14. The coating nozzle 21 may be, for example, a slit nozzle. The slit nozzle has a slit-shaped discharge port that is perpendicular to the longitudinal direction of the laminated substrate 9 and extends along the width direction, which is a horizontal direction.
[0031] The liquid supply pipe 22 is a flow path that connects the coating nozzle 21 and the catalyst ink supply source 23. The liquid supply pipe 22 is provided with an on-off valve 24. When the on-off valve 24 is opened, the catalyst ink is supplied from the catalyst ink supply source 23 to the coating nozzle 21 by the pressure of a pump (not shown) or pressure utilizing a head difference. Then, the catalyst ink is discharged from the discharge port of the coating nozzle 21 onto a first surface 911 of the electrolyte membrane 91 in the laminated base material 9 supported by the support roller 14. As a result, the catalyst ink is applied to the first surface 911 of the electrolyte membrane 91. The process in which the application unit 20 applies the catalyst ink to the electrolyte membrane 91 corresponds to the application process.
[0032] When the on-off valve 24 is opened and closed at a constant cycle, the catalyst ink is intermittently discharged from the discharge port of the coating nozzle 21. As a result, the catalyst ink is intermittently applied to the electrolyte membrane 91 at constant intervals in the transport direction. Note that the on-off valve 24 may be continuously opened, so that the catalyst ink is applied to the electrolyte membrane 91 without interruption in the transport direction.
[0033] It is not essential that the catalyst ink be applied to the laminated substrate 9 supported by the support roller 14. For example, the catalyst ink may be ejected onto a portion of the electrolyte membrane 91 that is stretched between two rollers that are spaced apart in the transport direction. The coating nozzle 21 may also eject the catalyst ink in a spray-like manner onto the electrolyte membrane 91.
[0034] The drying unit 30 is disposed downstream of the coating nozzle 21 on the transport path. The drying unit 30 has a drying furnace 31 for drying the catalyst ink. In the drying furnace 31, a heated gas (hot air) is blown onto the electrolyte membrane 91 of the laminated base material 9 transported by the transport mechanism 10. Then, the catalyst ink applied to the first surface 911 of the electrolyte membrane 91 is heated, and the solvent in the catalyst ink is vaporized. As a result, the catalyst ink is dried, and a catalyst layer 93 is formed on the first surface 911 of the electrolyte membrane 91. However, the method for drying the catalyst ink does not necessarily have to be the supply of hot air. The drying unit 30 may dry the catalyst ink by other methods such as light irradiation or reduced pressure. The process in which the drying unit 30 dries the catalyst ink applied to the electrolyte membrane 91 to form the catalyst layer 93 corresponds to the drying process.
[0035] The pressure heating section 40 is disposed downstream of the transport path from the drying section 30. The pressure heating section 40 is a mechanism for heating the laminated base material 9 while pressing it. The pressure heating section 40 has a pair of heat rollers 41, 41 and a heating section 43.
[0036] The pair of heat rollers 41, 41 rotate around a horizontal axis. The distance (roll gap) between the pair of heat rollers 41, 41 is adjusted to a value smaller than the thickness of the laminated base material 9. When the laminated base material 9 passes between the pair of heat rollers 41, 41, the laminated base material 9 is sandwiched between the pair of heat rollers 41, 41 and compressed.
[0037] Since the pair of hot rollers 41, 41 have the same structure, the configuration of one hot roller 41 will be described below. The hot roller 41 has a roller body 411 and a releasable surface member 413. The roller body 411 has a cylindrical shape with an outer surface formed of a metal such as SUS (stainless steel). The outer peripheral surface of the roller body 411 is covered with the releasable surface member 413. That is, the releasable surface member 413 is fixed to the outer surface of the roller body 411. The releasable surface member 413 is, for example, cylindrical. The adhesive force of the releasable surface member 413 to the electrolyte membrane 91 and the catalyst layer 93 is smaller than that of the roller body 411. The roller body 411 is an example of a "pressing body part". The releasable surface member 413 is an example of a "releasable member".
[0038] The thickness (average value) of the releasable surface member 413 is preferably 100 μm or more, and more preferably 200 μm or more. If the releasable surface member 413 is too thick, the uniformity of compression by the pair of heated rollers 41, 41 may be lost. From this perspective, the thickness of the releasable surface member 413 is preferably 500 μm or less, and more preferably 300 μm.
[0039] The material of the releasable surface member 413 is, for example, a heat-resistant polymer, specifically, PTFE (polytetrafluoroethylene), PFA (perfluoroalkoxyalkane), FEP (fluorinated ethylene propylene copolymer), PVDF (polyvinylidene fluoride), PEEK (aromatic polyether ketone), PI (polyimide), PBI (polybenzimidazole), PPS (polyphenylene sulfide), PEI (polyetherimide), or PSU (polysulfone). By using a heat-resistant polymer as the material of the releasable surface member 413, it is possible to provide the releasable surface member 413 with heat resistance (specifically, a heat-resistant temperature of 130° C. or higher, more preferably 150° C. or higher). Therefore, when the electrolyte membrane 91 is pressed, deformation of the releasable surface member 413 can be suppressed. The material of the releasable surface member 413 is not limited to a heat-resistant polymer. For example, the releasable surface member 413 may be a DLC (Diamond Like Carbon) coating on the outer surface of the roller body 411.
[0040] In the pair of heated rollers 41, 41, the roller body 411 presses the electrolyte membrane 91 via the releasable surface member 413, with the releasable surface member 413 in contact with the catalyst layer 93 or the electrolyte membrane 91. The heated roller 41 is an example of a pressing member.
[0041] The heating unit 43 is a mechanism for supplying power to a heater provided in each roller body 411 of the pair of heat rollers 41, 41. The heating unit 43 may be a mechanism for supplying heated liquid to a pipe built into the roller body 411. The heating unit 43 heats the surface temperature of the heat roller 41 to a predetermined temperature (for example, 50°C or higher and 180°C or lower). The laminated base material 9 is sandwiched between the pair of heat rollers 41 with their heated surfaces, whereby the electrolyte membrane 91 and catalyst layer 93 included in the laminated base material 9 are heated and compressed. In this way, the process in which the pressing and heating unit 40 presses and heats the electrolyte membrane 91 on which the catalyst layer 93 has been formed, with the pair of heat rollers 41, 41, corresponds to the pressing and heating process.
[0042] The adhesive strength of the heated roller 41 (specifically, the releasable surface member 413) to the catalyst layer 93 and electrolyte membrane 91 after drying by the drying unit 30 is 0.5 N / cm or less in a 180° peel test (ISO 29862:200). This can reduce the transfer of the catalyst layer 93 and the sticking of the electrolyte membrane 91 to the pressing member.
[0043] In the CCM manufacturing apparatus 1 of this embodiment, both of the pair of heated rollers 41 are provided with a releasable surface member 413. However, the heated roller 41 that comes into contact with the backsheet 92 does not necessarily need to have the releasable surface member 413.
[0044] Furthermore, the CCM manufacturing apparatus 1 includes two heat rollers 41, but may include three or more heat rollers 41.
[0045] Furthermore, it is not essential that the pressure heating section 40 is incorporated into the CCM production apparatus 1. In other words, the pressure heating section 40 may be incorporated into an apparatus separate from the coating section 20 and the drying section 30.
[0046] Furthermore, although the CCM production apparatus 1 is configured to perform coating on only one side, it may be configured to perform double-sided coating.
[0047] <2. Second embodiment> Next, a second embodiment will be described. In the following description, elements having the same functions as elements already described will be given the same reference numerals or reference numerals with an additional alphabetical character, and detailed description thereof may be omitted.
[0048] 2 is a diagram showing a CCM manufacturing apparatus 1A according to a second embodiment. The CCM manufacturing apparatus 1A differs from the CCM manufacturing apparatus 1 shown in FIG. 1 in that it includes a pressure heating unit 40A instead of the pressure heating unit 40. The pressure heating unit 40A includes a pair of heat rollers 41A, 41A and a release sheet supply unit 45.
[0049] The hot roller 41A is different from the hot roller 41 of the first embodiment in that it does not include a release surface member 413 and the outer surface of the roller body 411 is exposed to the outside. The release sheet supply unit 45 is a mechanism that supplies the release sheet 415 between the pair of hot rollers 41A, 41A. The release sheet 415 is a strip-shaped sheet member. Like the release surface member 413, the release sheet 415 is a release member whose adhesive force to the first surface 911 of the electrolyte membrane 91 and the catalyst layer 93 is smaller than that of the roller body 411. The release sheet 415 is formed of the same material as the release surface member 413 of the hot roller 41 shown in FIG. 1. That is, the material of the release sheet 415 can be PTFE, PFA, FEP, PVDF, PEEK, PI, PBI, PPS, PEI, or PSU.
[0050] The release sheet supply unit 45 has an unwinding roller 451, a plurality of transport rollers 452, and a take-up roller 453. The unwinding roller 451, the transport rollers 452, and the take-up roller 453 rotate about a horizontal axis.
[0051] The release sheet 415 is wound in a roll around the unwinding roller 451. Each transport roller 452 supports the unwinding roller 451 and guides it to the winding roller 453. In this example, a pair of heat rollers 41A, 41A are disposed between the pair of transport rollers 452, 452. The portion of the release sheet 415 that is stretched across the pair of transport rollers 452, 452 is supplied between the pair of heat rollers 41A, 41A. After transport, the release sheet 415 is wound around the winding roller 453.
[0052] The adhesive strength of the release sheet 415 to the electrolyte membrane 91 and catalyst layer 93 (specifically, to the catalyst layer 93 after drying by the drying unit 30) is 0.5 N / cm or less in a 180° peel test (ISO 29862:200).
[0053] The thickness (average value) of release sheet 415 is preferably 100 μm or more, and more preferably 200 μm or more. If release sheet 415 is too thick, the uniformity of compression by the pair of heat rollers 41, 41 may be lost. From this viewpoint, the thickness of release sheet 415 is preferably 500 μm or less, and more preferably 300 μm or less.
[0054] 2, the release sheet supplying unit 45 supplies the release sheet 415 only between the laminated base material 9 and the heat roller 41A on the electrolyte membrane 91 side (i.e., the first surface 911 side on which the catalyst layer 93 is formed) of the laminated base material 9. However, a release sheet supplying unit 45 that supplies the release sheet 415 may also be provided between the laminated base material 9 and the heat roller 41A on the back sheet 92 side of the laminated base material 9.
[0055] Also, instead of heated roller 41A, heated roller 41 having a releasable surface member 413 as shown in FIG. 1 may be used.
[0056] It is not essential that the pressure and heating section 40A is incorporated in the CCM production apparatus 1. In other words, the pressure and heating section 40A may be incorporated in an apparatus separate from the coating section 20 and the drying section 30.
[0057] In the CCM manufacturing apparatus 1A, a roll of release sheet 415 is supplied, but this is not essential. For example, if the press heating unit 40A is provided separately from the CCM manufacturing apparatus 1, a release sheet processed into a rectangular shape may be sandwiched between the heat roller 41A and the catalyst layer 93. This method is particularly effective in the case of small-scale production.
[0058] <3. Experimental Example> Next, an experimental example that demonstrates the effects of each of the above-mentioned embodiments will be described. Table 1 shows the evaluation results of the transfer of the catalyst layer to the heat roller and the evaluation results of the adhesion of the electrolyte membrane to the heat roller when a heat pressing process is performed using an apparatus with a similar configuration to the CCM manufacturing apparatus 1 or 1A. Note that an electrolyte membrane with a PET back sheet attached thereto was used as the laminated substrate. The conveying speed of the laminated substrate was set to 1 m / min.
[0059] [Table 1]
[0060] When the temperature of the hot roller was low (100°C) as in Comparative Example 1, the adhesion of the catalyst ink could not be sufficiently improved. Also, as in Comparative Examples 2 to 5, the adhesion of the catalyst ink could be improved by setting the temperature of the hot roller to 120°C or higher (above the glass transition temperature of the ionomer), but when the surface material of the hot roller was SUS, which has low releasability, the transfer of the catalyst layer to the hot roller and the sticking of the electrolyte membrane to the hot roller occurred. On the other hand, when the surface material of the hot roller was PTFE as in Examples 1 to 3, or when a PTFE release sheet was sandwiched between the hot roller and the electrolyte membrane, the transfer of the catalyst layer to the hot roller and the sticking of the electrolyte membrane to the hot roller could be avoided even if the temperature of the hot roller was 160°C.
[0061] Tables 2 and 3 show the evaluation results for the surface material of the heat roller. Here, (1) the adhesion of the electrolyte membrane was evaluated, and (2) the adhesion and transfer rate of the catalyst layer were evaluated. Each evaluation was performed according to the following procedure.
[0062] (1) Procedure for evaluating the adhesion of electrolyte membrane Step 1. Prepare an electrolyte membrane and flat plates with different surface materials. Step 2. Heat the above plate to 140°C. Step 3: Place the electrolyte membrane (2 cm x 10 cm) on a flat plate heated to 140°C, and press the electrolyte membrane against the flat plate with a pressure of 2 MPa for 10 seconds. Step 4. Connect the end of the electrolyte membrane to a force gauge and hold it. Measure the peel force when peeling the electrolyte membrane from the flat plate at a peel angle of 180° and a peel speed of 300 mm / min. The measured peel force is defined as the adhesive strength of the electrolyte membrane.
[0063] (2) Procedure for evaluating the adhesion and transfer rate of the catalyst layer Step 1. Prepare an electrolyte membrane with a catalyst layer and flat plates with different surface materials. Step 2. Heat the above plate to 140°C. Step 3: Place the electrolyte membrane (2 cm x 10 cm) on a flat plate heated to 140° C., with the surface on which the catalyst layer is formed being in contact with the flat plate. Press the electrolyte membrane against the flat plate at a pressure of 2 MPa for 10 seconds. Step 4. The edge of the electrolyte membrane is connected to a force gauge and held, and the peel force is measured when peeling the electrolyte membrane with catalyst layer from the flat plate at a peel angle of 180° and a peel speed of 300 mm / min. The measured peel force is defined as the adhesive strength of the catalyst layer. Step 5: If the catalyst layer is transferred to a flat plate, measure the weight of the catalyst layer transferred to the flat plate and calculate the weight ratio (%) of the transferred catalyst layer to the total catalyst layer. This value is defined as the transfer rate to the heat roller.
[0064] After the above evaluation, the deformation state of the surface of the flat plate was confirmed (deformation evaluation). In addition, it was evaluated whether the CCM manufacturing device 1 equipped with the heat roller 41 of each surface material could be transported at a transport tension of 1.0 N / cm (transportability).
[0065] [Table 2]
[0066] [Table 3]
[0067] In the case of Comparative Examples 6 and 7, when the surface material of the flat plate was SUS or silicone rubber, both the adhesion strength of the electrolyte membrane and the adhesion strength of the catalyst layer exceeded 0.5 N / cm. In addition, transportation in the CCM manufacturing equipment 1 was difficult, and the catalyst layer was also transferred to the heat roller.
[0068] Furthermore, when the surface material was PET as in Comparative Example 8, the surface of the plate was physically indented by the pressure of the electrolyte membrane pressed against the plate. This is believed to be due to the fact that the heat resistance temperature of PET is not high.
[0069] On the other hand, in the case of surface materials with high releasability as in Examples 4 to 14, the adhesion strength of the electrolyte membrane and catalyst layer was 0.5 N / cm or less in all cases. In addition, in all cases, transportation was possible in the CCM manufacturing equipment 1, and the catalyst layer transfer was 0%. Furthermore, in all cases, no deformation of the flat plate occurred.
[0070] As is clear from the above results, by setting the adhesion (adhesion) of the pressing member to the electrolyte membrane and catalyst layer to 0.5 N / cm or less, the transfer of the catalyst layer to the pressing member and its sticking to the pressing member can be prevented.
[0071] Although the present invention has been described in detail, the above description is merely illustrative in all respects, and the present invention is not limited thereto. It is understood that countless variations not illustrated can be envisioned without departing from the scope of the present invention. The configurations described in the above embodiments and variations can be appropriately combined or omitted as long as they are not mutually contradictory. [Explanation of symbols]
[0072] 1, 1A:CCM manufacturing equipment 9: Laminated base material 10: Transport mechanism 20: Application section 30:Drying section 40, 40A: Pressurized heating section 41: Heat roller (pressure member) 43: Heating section 91: Electrolyte membrane 93: Catalyst layer 411: Roller body (pressing body part) 413: Releaseable surface material (Releasable material) 415: Release sheet
Claims
1. a coating step of coating the electrolyte membrane with a catalyst ink; a drying step of drying the catalyst ink applied to the electrolyte membrane in the application step to form a catalyst layer; a pressing and heating step of pressing the electrolyte membrane having the catalyst layer formed thereon with a pressing member and heating the electrolyte membrane after the drying step; Including, The method for producing a membrane / catalyst layer assembly, wherein the adhesive strength of the pressing member to the electrolyte membrane and the catalyst layer is 0.5 N / cm or less.
2. A method for producing the membrane / catalyst layer assembly according to claim 1, comprising the steps of: the pressing member has a pressing body and a releasable member having an adhesive force to the electrolyte membrane and the catalyst layer that is smaller than that of the pressing body, The method for producing a membrane / catalyst layer assembly, wherein the pressing member presses the electrolyte membrane via the pressing main body with the releasable member in contact with the electrolyte membrane.
3. A method for producing the membrane / catalyst layer assembly according to claim 2, comprising the steps of: The method for producing a catalyst-coated membrane assembly, wherein the releasable member is fixed to a surface of the pressing body.
4. A method for producing the membrane / catalyst layer assembly according to claim 2 or 3, comprising the steps of: the releasable member is a sheet-shaped release sheet, The press-heat step includes a step of supplying the release sheet between the catalyst layer and the electrolyte membrane and the press body.
5. A method for producing the membrane / catalyst layer assembly according to claim 3, comprising the steps of: A method for producing a membrane / catalyst layer assembly, wherein the material of the releasable member contains a heat-resistant polymer.
6. A method for producing the membrane / catalyst layer assembly according to claim 3, comprising the steps of: The pressing body includes a pair of heat rollers whose surfaces are heated, The press-heat step includes a step of sandwiching the catalyst layer and the electrolyte membrane between the pair of heat rollers.
7. An apparatus for manufacturing a membrane catalyst layer assembly, comprising: a transport mechanism for transporting the electrolyte membrane; an application unit that applies a catalyst ink to the electrolyte membrane being transported by the transport mechanism; a drying section for drying the catalyst ink applied by the application section to form a catalyst layer; a pressing and heating unit that presses and heats the catalyst layer and the electrolyte membrane with a pressing member; Equipped with an adhesive strength of the pressing member to the catalyst layer and the electrolyte membrane is 0.5 N / cm or less;
Citation Information
Patent Citations
Electrolyte membrane modification device and electrolyte membrane modification method, and production system and production method of membrane / catalyst layer assembly
JP2015153653A